THE TEACHER’S ROLE IN SHAPING LEARNING INDEPENDENCE STUDENTS TROUGH THE HABITUATION LEARNING METHOD - Yuni Agustina; Firman; Riska Ahmad (Literasi Nusantara, 2021)
This article uses references from related literature studies to discuss the role of teachers in forming student learning independence through habituation learning methods, where student learning independence is the ability of students to carry out learning activities that are focused on activity, responsibility, and a high willingness to do something. without asking others for help. To get the expected learning outcomes, serious thinking is needed, so that the material presented is well received and understood by students. Therefore, every learning process that is designed and organized must have a contribution to achieve the expected goals, the teacher must choose an appropriate learning method, one of which is the habituation learning method to increase student learning independence. The habituation method is a method in education in the form of a process of inculcating habits. The essence of habituation is repetition.